Hospital de pequeno porte : existir, a que será que se destina? Internações e perfil no Espírito Santo - Araujo, Tânia Maria de (2008)
The so called small hospitals had a specific policy established by the Health Department in June, 2004 and it was evidenced that the insertion of those hospitals in the health system would have as line of direction the support to basic attention, aiming at printing a greater resolution to this level. Questionnaires about he capacity to solve the services offered by such hospitals are made, besides presenting an expensive structure. However, located in the countryside, are mostly considered the main or the only reference for urgency and emergency and  internment, reasons why the population go there for several health problems. The worry concerning the performance of such hospitals brought to the present study the objectives; studying the tendency of the internments in the districts containing small hospitals during 1992 and 2005; delineating a profile of small hospitals taking into account structural and assistant characteristics and characterizing the internment causes that took place in the districts containing small hospitals in 2005. The study objects were: the small hospitals with up to 50 beds, public or private belonging to SUS and located in Espírito Santo districts with up to 30 thousand habitants. The research was descriptive and quantitative. The results showed the presence of some district studied (61,5%) having a negative tendency internments in the period analyzed, considering that in the profile of the hospitals it was observed the private nature of organizations and the necessity of equipments and the installation related to the hospital assistance. For the majority of the districts, the internments for sensitive conditions to the ambulatory attention presented superior percentages to the state and de main causes were gastroenterites, pneumonia, heart failure, hypertension and asthma. This research indicate that the redefinition of profile and role of small hospital is necessary and important to the health care system.